2019
DOI: 10.1111/1346-8138.14815
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐17 receptor A blockade with brodalumab in palmoplantar pustular psoriasis: Report on four cases

Abstract: Palmoplantar pustular psoriasis, also termed palmoplantar pustulosis (PPP), is a rare disease affecting the palmoplantar regions characterized by sterile, yellow to brown pustules mostly on erythematous skin. PPP is related to a high burden due to painful, impaired and stigmatizing character. Several isoforms of interleukin (IL) have been implicated in its pathophysiology. Here, we report on four patients with PPP treated with the novel IL‐17 receptor A blocker brodalumab, in whom this therapy was not successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Among the IL-17 inhibitors, secukinumab and brodalumab have been investigated for the treatment of PPP [108,109]. In a multicenter, randomized, double-blind clinical trial (2PRECISE) involving over 200 patients with PPP, secukinumab 300 mg and 150 mg were compared with placebo in the treatment of PPP.…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the IL-17 inhibitors, secukinumab and brodalumab have been investigated for the treatment of PPP [108,109]. In a multicenter, randomized, double-blind clinical trial (2PRECISE) involving over 200 patients with PPP, secukinumab 300 mg and 150 mg were compared with placebo in the treatment of PPP.…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…At week 52, a total of 41.8% of the patients receiving secukinumab 300 mg reached PPPASI-75, and 43.1% had a DLQI response of 0 or 1 [108]. A case series of four patients receiving brodalumab reported a lack of efficacy or moderate improvement in the treatment of PPP [109]. A phase III placebo-controlled study on the efficacy of brodalumab in subjects with PPP is ongoing ( Table 2).…”
Section: Il-17 Inhibitorsmentioning
confidence: 99%
“…The IL-17 inhibitor secukinumab has also been evaluated for moderate-to-severe PPP, but did not demonstrate superiority versus placebo in achievement of the primary endpoint (75% improvement from baseline in Palmoplantar Pustulosis Psoriasis Area and Severity Index [PPPASI]) [54]. Brodalumab, another IL-17 inhibitor, has been evaluated in PPP and has demonstrated either no improvement or moderate improvement in a recent case series of treated patients [55]. A small (N = 15), randomized, placebo-controlled, prospective study of a TNFa inhibitor, etanercept, has shown mixed results, with some patients experiencing improvements and others showing worsening PPP [56].…”
Section: Treatment Optionsmentioning
confidence: 99%
“…But, in the long-term, at week 52, non-responders of the secukinumab and the placebo arms were treated with 300 mg every 4 weeks with 42% PPPASI-75 efficacy and 150 mg with 35% PPPASI-75 efficacy 54 . Only case reports regarding other anti-IL-17 therapies are available, with lack of efficacy of brodalumab in four PPP cases, but a phase III RCT is ongoing 43 , 55 .…”
Section: New Therapeutic Optionsmentioning
confidence: 99%